Implementasi Metode Eklektik Berbasis Kurikulum 2013 pada Pembelajaran Bahasa Arab di madrasah Tsanawiyah DDI Padanglampe-Pangkep - Hafid, Wahyudin; Syarifuddin , Said; Sultan, Nurlaelah (Shaut al Arabiyyah, 2023)
This research aims to photograph the phenomenon of implementing eclectic methods based on the 2013 Curriculum in Arabic language learning at Madrasah Tsanawiyah DDI Padanglampe- Pangkep, regency with 3 discussion focuses; preparation, implementation and evaluation processes. Methodologically, this research is descriptive-qualitative with a phenomenological approach. Data was obtained by field studies which were strengthened by research instruments; documentation, observation and structured interviews with informant sources selected randomly and simply from madrasah; madrasah head, Arabic teacher and students. The research findings data were analyzed descriptively and presented using Miles and Hubermen's Theory. The results of the research show that learning Arabic at MTs DDI Padanglampe using an eclectic method based on the 2013 Curriculum is going WELL. Learning activities include preparation, process and evaluation based on the parameters of the 2013 Curriculum. Learning Arabic in Madrasas includes memorizing vocabulary (mufradat), learning qiraah and kitabah, and language structure (tarkib) even though it is still in simple and simple descriptions. Although it is acknowledged that various obstacles are still found in the learning process, both internal and external factors.